Possible Involvement of Nitric Oxide Modulatory Mechanisms in the Neuroprotective Effect of Centella asiatica Against Sleep Deprivation Induced Anxiety Like Behaviour, Oxidative Damage and Neuroinflammation. (5th February 2016) - Chanana, Priyanka; Kumar, Anil
Abstract : Sleep deprivation (SD) is an experience of inadequate or poor quality of sleep that may produce significant alterations in multiple neural systems. Centella asiatica (CA) is a psychoactive medicinal herb with immense therapeutic potential. The present study was designed to explore the possible nitric oxide (NO) modulatory mechanism in the neuroprotective effect of CA against SD induced anxiety like behaviour, oxidative damage and neuroinflammation. Male laca mice were sleep deprived for 72 h, and CA (150 and 300 mg/kg) was administered alone and in combination with NO modulators for 8 days, starting five days before 72‐h SD exposure. Various behavioural (locomotor activity, elevated plus maze) and biochemical (lipid peroxidation, reduced glutathione, catalase, nitrite levels and superoxide dismutase activity), neuroinflammation marker (TNF‐alpha) were assessed subsequently. CA (150 and 300 mg/kg) treatment for 8 days significantly improved locomotor activity, anti‐anxiety like effect and attenuated oxidative damage and TNF α level as compared to sleep‐deprived 72‐h group. Also while the neuroprotective effect of CA was increased by NO antagonists, it was diminished by NO agonists. The present study suggests that NO modulatory mechanism could be involved in the protective effect of CA against SD‐induced anxiety‐like behaviour, oxidative damage and neuroinflammation in mice. Copyright © 2016 John Wiley & Sons, Ltd.